A violent spectacle : terrorism in contemporary Peninsular drama - Downs, Tara (Madrid : Iberoamericana ; Frankfurt am Main : Vervuert, 2019)
Terrorism has long been a part of Spanish history, although the 1990s and early 21st century brought some changes in terms of who committed the attacks and how. Other changes that took place at this time include the increasing openness about terrorism in theatre. What is it about this time period that led to the new ways of discussing and approaching violence/terrorism? Was it more frequent? or simply less covert? This book examines the intersection of violence and theatre in Spain, in addition to the role this cultural combination plays on the identity and quotidian experience of the Spanish people, through the study of dramas by contemporary playwrights Ignacio Amestoy, Koldo Barrena, Sergi Belbel, Fermín Cabal, Jordi Galceran, Juan Alberto López and Alfonso Sastre.
Incluye referencias bibliográficas (páginas 155-167) e índice.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2020. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Terrorism in literature; Violence in literature; Spanish drama -- 20th century -- History and criticism; Spanish drama -- 21st century -- History and criticism; Catalan drama -- 21st century -- History and criticism; Terrorismo en la literatura; Violencia en la literatura; Drama español -- Siglo XX -- Historia y crítica.; Drama español -- Siglo XXI -- Historia y crítica.; Drama catalán -- Siglo XXI -- Historia y crítica.; Libros electrónicos.